Model Pembelajaran Bahasa Arab di Ma’had Al-Jami’ah Walisongo Semarang - Shiddiq, Jamaluddin (IAIN Salatiga, 2018)
This study discusses the models of Arabic teaching in Ma’had Al-Jami’ah Walisongo Semarang. The analysis based on the Richard Arend’s theory, which is mentions that the teaching models has 4 components are theoretical basis, instructional goals, syntax, and learning environment. This study aims to know each component of it in ma’had. The study result shows that the theoretical basis of teaching includes behavioral theory, social learning theory, the psychological theory of meaningfull verbal learning, the idea of cognitive pshycology, experiential learning theory, and information processing theory. The Instructional goal includes the learning to acquire the factual and declare knowledge, mastering of social cooperative behaviors, and acceptance between groups. The syntax be distinguished by the type of teaching models, include: a) Direct teaching, consists of the orientation, presentation, structured practice, the practice under guidance, and self-practice, b) Presentation teaching, consists of presenting advance organizer, task presentation and strengthening cognitive processing; c) cooperative learning, consists of presenting the goal and establishing set, presenting and organizing information, distributing some students into groups, supporting the team work and teaching, testing the material learning and giving a testing; 4) learning environment in ma’had, includes: in the direct, the teacher structures the environment stricty to maintain the academic focuses and hopes the tudents will be a good observer, listener and participant; b) in the presentation: the teacher distributing, some students into a group and in each gropu, there is two role, presentator and listener; c) cooperative: the environment organized based on task structure and reward cooperatively neither competitively.